Growth Differentiation Factor-11 Causes Neurotoxicity During Ischemia in vitro - Sutherland, Brad A.; Hadley, Gina; Alexopoulou, Zoi; Lodge, Tiffany A.; Neuhaus, Ain A.; Couch, Yvonne; Kalajian, Nareg; Morten, Karl J.; Buchan, Alastair M. (Frontiers in Neurology, 2020)
Age-related neuronal dysfunction can be overcome by circulating factors present in young blood. Growth differentiation factor-11 (GDF-11), a systemic factor that declines with age, can reverse age-related dysfunction in brain, heart and skeletal muscle. Given that age increases susceptibility to stroke, we hypothesised that GDF-11 may be directly protective to neurons following ischemia. Primary cortical neurons were isolated from E18 Wistar rat embryos and cultured for 7-10 days. Neurons were deprived of oxygen and glucose (OGD) to simulate ischemia. Neuronal death was assessed by lactate dehydrogenase, propidium iodide or CellTox™ green cytotoxicity assays. 40ng/mL GDF-11 administration during 2h OGD significantly increased neuronal death following 24h recovery. However, GDF-11 pre-treatment did not affect neuronal death during 2h OGD. GDF-11 treatment during the 24h recovery period after 2h OGD also did not alter death. Real-time monitoring for 24h revealed that by 2h OGD, GDF-11 treatment had increased neuronal death which remained raised at 24h. Co-treatment of 1μM SB431542 (ALK4/5/7 receptor inhibitor) with GDF-11 prevented GDF-11 neurotoxicity after 2h OGD and 24h OGD. Transforming growth factor beta (TGFβ) did not increase neuronal death to the same extent as GDF-11 following OGD. GDF-11 neurotoxicity was also exhibited following neuronal exposure to hydrogen peroxide. These results reveal for the first time that GDF-11 is neurotoxic to primary neurons in the acute phase of simulated stroke through primarily ALK4 receptor signalling.